Who Are Our Fans: An Application of Principal Component-Cluster Technique Analysis to Market Segmentation of College Football Fans - DANIEL A RASCHER; Kenneth Cortsen; Mark S Nagel; Tiffany Richardson (Journal of Applied Sports Management, 2021)
A 66-question online marketing survey of 2,800 football fans who had purchased tickets to a Division I, Power 5 (P5) university football game was conducted in order to understand the fan base and provide better services and targeted marketing. Principal Component Analysis was employed to combine responses from multiple questions about purchase behavior, on-site satisfaction, demographics, and other criteria. Subsequent market segmentation via cluster analysis indicated that 95% of the survey respondents could be categorized into one of five clusters. The identified fan perceptions and evaluations resulted in the P5 athletic department taking specific actions to improve targeted marketing activities and enhance game-day experiences, including improving the quality and diversity of food offerings, ensuring smoother ingress and egress, offering more precise ticket packages, and targeting groups through relevant marketing channels. The current research notes the importance of utilizing precision marketing efforts to target specific clusters and then providing appropriate tangible and intangible products and services to maximize initial sales, improve fan experience, and increase the likelihood of repeat purchases.
Keywords: cluster analysis; principal component analysis; market segmentation; college football fans; survey; sport business analytics